1999
DOI: 10.1177/082957359901400203
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Children's Handwriting Under Traditional vs. Whole Language Instruction

Abstract: The current study compared the speed and legibility of handwriting produced by children exposed to either traditional instruction (TI) or whole-language instruction (WLI) in an attempt to determine whether children who received traditional, intensive classroom instruction in handwriting produce more legible andfaster handwriting. Forty-four TI students in lower (4 & 5) and upper (7 & 8) grades were matched with WLI students on the basis of chronological age, sex, grade, and dominant hand. All participants prov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2007
2007
2010
2010

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…The quality of handwriting may influence academic outcomes, with higher marks assigned for neatly written papers (Sweedler-Brown, 1992). The nature and extent of instruction affects a student's ability to perform skilled handwriting, with explicit instruction increasing the legibility and efficiency of written work (Goldberg & Simner, 1999), as well as improving composition skills (Berninger et al, 1997;Graham, Harris, & Fink, 2000). Cursive script, in which the letters within words are connected by joined strokes, has been traditionally reported to be the form of writing preferred for efficiency in legibility and speed, although controversy does exist .…”
mentioning
confidence: 99%
“…The quality of handwriting may influence academic outcomes, with higher marks assigned for neatly written papers (Sweedler-Brown, 1992). The nature and extent of instruction affects a student's ability to perform skilled handwriting, with explicit instruction increasing the legibility and efficiency of written work (Goldberg & Simner, 1999), as well as improving composition skills (Berninger et al, 1997;Graham, Harris, & Fink, 2000). Cursive script, in which the letters within words are connected by joined strokes, has been traditionally reported to be the form of writing preferred for efficiency in legibility and speed, although controversy does exist .…”
mentioning
confidence: 99%
“…The authors explained these findings by the fact that in the higher grades, teachers focus mainly on higher-level and more complex writing tasks and therefore devote less time and energy to monitoring the quality of students' handwriting. In relation to gender differences, studies have shown that girls' handwriting is more legible than that of boys both in elementary school (Berninger & Fuller, 1992;Goldberg & Simner, 1999;Weintraub & Graham, 2000;Yochman & Parush, 1998) and in middle school (Graham et al, 1998;Hooper et al, 1993).…”
Section: Relationship Between Age Gender and Handwriting Performancementioning
confidence: 99%